STUDI ANALISIS DAMPAK PADEMI COVID-19 TERHADAP EKSISTENSI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI INDONESIA - ilzam dhaifi (Fakultas Tarbiyah, Universitas Ibrahimy, 2020)
The world has been surprised by the emergence of a COVID 19 pandemic, was born in China, and widespread to various countries in the world. In Indonesia, the government issued several policies to break the COVID 19 pandemic chain, which also triggered some pro-cons in the midst of society. One of the policies government takes is the closure of learning access directly at school and moving the learning process from physical class to a virtual classroom or known as online learning. In the economic sector also affects the parents’ financial ability to provide sufficient funds to support the implementation of distance learning applied by the government. The implications of the distance education policy are of course the quality of learning, including the subjects of Islamic religious education, which is essentially aimed at planting knowledge, skills, and religious consciousness to form the character of the students. Online education must certainly be precise, in order to provide equal education services to all students, prepare teachers to master the technology, and seek the core learning of Islamic religious education can still be done well.